Les gisements précolombiens de la Baie Orientale Campements du Mésoindien et du Néoindien sur l'île de Saint-Martin (Petites Antilles) - Bonnissent, Dominique (Documents d'archéologie française, 2013)
Two exceptionally well preserved sites were discovered in 2000 on the backshore of Baie Orientale on the island of Saint Martin, Lesser Antilles: Mesoindian camps (800 BC - 100 AD), where subsistence activities were associated with stone, shell and coral tool manufacturing, which was previously unknown for the Preceramic period, and a Early Neoindian site (740-960 AD) interpreted as a specialized satellite camp of the village of Pointe du Canonnier, thus corresponding to a territorial settlement pattern that is characteristic of this period. The innovative and original study proposed by Dominique Bonnissent sheds light on the complex lifestyle of the nomadic Preceramic populations that moved about the Caribbean Ocean. This work henceforth provides an indispensible resource for Caribbean Pre-Columbian archaeology. At the beginning of each chapter, a substantial summary with bibliographic references and figure citations allow English and Spanish speaking readers to consult the essential data and arguments.